2018
DOI: 10.1007/s00277-018-3393-7
|View full text |Cite
|
Sign up to set email alerts
|

High chymotrypsin-like activity in the plasma of patients with newly diagnosed multiple myeloma treated with bortezomib is predictive of a better response and longer PFS

Abstract: Proteasome inhibitors (PIs) such as bortezomib constitute an important part of the modern standard therapy for multiple myeloma (MM). In this study, we set out to assess whether proteasome concentration and chymotrypsin-like (ChT-L) activity could serve as potential biomarkers defining the likelihood of response to treatment with bortezomib, in order to identify patients who are more likely to respond to treatment with PI. We analysed proteasome concentration and ChT-L activity in the plasma of 78 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The proteasome inhibitor carfilzomib impairs the recycling of misfolded proteins, leading to ER stress and cell death. Over the past 20 years, inhibition of the proteasome chymotrypsin‐like activity has shown clinical efficacy in patients with hematological malignancies [ 39 ]. More recently, a preclinical work has provided evidence that carfilzomib may have activity also in solid tumors [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The proteasome inhibitor carfilzomib impairs the recycling of misfolded proteins, leading to ER stress and cell death. Over the past 20 years, inhibition of the proteasome chymotrypsin‐like activity has shown clinical efficacy in patients with hematological malignancies [ 39 ]. More recently, a preclinical work has provided evidence that carfilzomib may have activity also in solid tumors [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Enzymatically active extracellular proteasomes have also been revealed in human plasma and cerebrospinal fluid [8][9][10]. Proteomic analysis of affinity-purified extracellular proteasomes revealed that extracellular proteasomes do not contain 19S or PA200 regulatory particles and are represented exclusively by the 20S complex [11].…”
Section: Introductionmentioning
confidence: 99%